PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 003 PULAU JAMBU - Nurli Rosmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the results of learning mathematics students class SD Negeri 003 Pulau Jambu, Kecamatan Cerenti, Kabupaten Kuantan Singingi which is still very low. This study aims to improve the results of learning mathematic on the subject of angles, circumference of square and rectangle. This study is a classroom action research conducted in two cycles, each cycle is implemented with four stages, namely: planning, implementation, observation and reflection. From the data analysis, there is an increase of both teacher activity, student activity, and student learning result. The teacher activity at the 1st cycle of percentage is 75% (Good) and at the 2nd meeting it increases 5% to 80% (Very Good). The average percentage of teacher activity in cycle I was 77.5% (Good). In the second cycle of the 3rd meeting increased by 10% from 80% (Good) to 90% (Very Good) and at 4th meeting increased by 5% from 90% (Very Good) to 95% (Very Good). The average Percentage of teacher activity in cycle II was 92.5% (Very Good). Judging from the student activity also increased from the 1st cycle meeting I was 60% (Enough) and at the 2nd meeting increased 15% to 75% (Good). The average percentage of student activity in cycle I was 67.5% (Enough). In the second cycle of meeting 3 it increases 10% from 75% (Good) to 85% (Very Good) and at 4th meeting increases 5% from 85% (Very Good) to 90% (Very Good). The average of student activity percentage in cycle II is 87,5% (Very Good). The average base score of 51.88 increased to 68.44 in the first cycle of the increase of 16.56 points and then in the second cycle increased to 88.75 on the second cycle of large increase of 36.87 points. From the data analysis there is an increase both from teacher activity, student activity, and student learning outcomes. It can be concluded that the enforcement of direct learning model can improve student learning outcomes mathematics class III SD Negeri 003 Pulau Jambu, Kecamatan Cerenti, Kabupaten Kuantan Singingi.